(untitled) (Research, Society and Development, 2019)
Occupational psychosocial risks (ROP) are constituted by a set of factors that alter the worker’s well-being, in relation to the work environment in which it operates. There are many complaints of psychic motivations that end up engendering pathologies at the corporal level, especially with regard to the teaching work of basic education. Usually, these professionals have multiple factors for constant health absences and frequent complaints of stress, generalized bodily pain, fatigue and depression, possibly resulting from a labor activity of constant disapproval and devaluation in today’s society. The objective of the study is to identify the existence of ROP in the work environment of primary school teachers and its repercussions on the mental health of these workers. Participated in the survey 7 teachers of basic education of a municipal school in Itabira. The study was based theoretically on the ergonomic perspective and was methodologically based on the assumptions of the qualitative research, having as methodological procedures the bibliographic research and the field research. A questionnaire was used as information collection technique. The results of the questionnaire indicated an index of 100% of the sample in agreement with regard to the psychosocial risks present in the working conditions. Regarding the variable quality of life and health, the results revealed significant relationships between absence of work and health. It is remarkable a mix of psychological and sociological factors that intersect generating the sickness of the teacher.